Discerning the mystical wisdom of the Bhagavad Gita and John of the Cross - C. Kourie (Acta Theologica)
The 21st century is characterised by a global spirituality. Presently, and more than ever, access to the great religious traditions has enabled many to tap into the wisdom of other cultures. While the respective epistemological foundations of diverse traditions may differ, mutual understanding and respectful dialogue nevertheless facilitate respect for the other and offer opportunities for mutual enrichment. This leads to the recognition that there are multiple dimensions and expressions of the sacred. From within this interspiritual approach, an analysis of the mystical wisdom of the Bhagavad Gita and John of the Cross clearly points to the central theme of discerning the real from the unreal. This leads to detachment from/lack of desire for and, finally, surrender to the Divine.